Heat penetration studies in the spin-processing of canned guayabano (soursop) mango and papaya juices (Anona muricata Linn., Mangifera indica Linn., and Carica papaya Linn.) - Matanguihan, Eleuteria L. 1936- (1969)
Heat penetration studies were conducted on the processing of canned guayabano (soursop), mango and papaya juices using both the spin and the static methods. The rates of heat transfer were compared in the two methods and the spin method was found to be approximately six times faster than the static method. For size No. 2 can it was found that 1-1/2 minutes processing was equivalent to 12 minutes static cooling, the latter by immersion of the canned product in a cooling tank. A chosen panel of six members was asked to evaluate the color, aroma and flavour of the products of both processes. The spin-processed products were rated favourably than the static method in all the 3 aspects of fruit juice quality. It was also found that the spin processing slightly improved the ascorbic acid retention of the mango and papaya juices but not improvement was noted in the guayabano juice.